1969
DOI: 10.1002/ardp.19693020304
|View full text |Cite
|
Sign up to set email alerts
|

Die kernresonanzspektrographische Untersuchung der Assoziation von Coffein mit Natriumbenzoat und einigen anderen Verbindungen

Abstract: Die Protonenresonanzsignale der drei Methylgruppen des Coffeins werden in wäßriger Lösung durch zugesetztes Natriumbenzoat stark verschoben. Die Abhängigkeit der chemischen Verschiebungen vom Benzoatzusatz ergibt s‐förmige Kurven, die auf das Zusammenwirken zweier magnetisch entgegengesetzt wirksamer Effekte hinweisen. Die beiden Effekte werden in der Fremdassoziation und in der Depolymerisation des Coffeins gesehen. Da in Chloroform Coffein keine Selbstassoziation eingeht und demnach auch nicht depolymerisier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…When sodium benzoate is added to a solution of theophylline, all three signals in the NMR spectrum move upfield. Stamm (11) observed a similar effect upon the interaction of sodium benzoate with caffeine. Figure 1 shows the induced chemical shift change for the two methyl groups of theophylline as a function of sodium benzoate concentration.…”
Section: Resultsmentioning
confidence: 72%
“…When sodium benzoate is added to a solution of theophylline, all three signals in the NMR spectrum move upfield. Stamm (11) observed a similar effect upon the interaction of sodium benzoate with caffeine. Figure 1 shows the induced chemical shift change for the two methyl groups of theophylline as a function of sodium benzoate concentration.…”
Section: Resultsmentioning
confidence: 72%
“…Recent reviews (3,4) indicated that no reports have appeared for testing tetrazole analogs of amino acids for antineoplastic activity. Studies of the biological activity of 5-substituted tetrazoles have been prompted by a close similarity between the acidity of the tetrazole group and the carboxylic acid group, and the fact that the tetrazole function appears to be metabolically more stable (3).…”
Section: -Ch3; and 0 7 -C Hmentioning
confidence: 99%